HUBUNGAN PELAYANAN, CITRA, DAN LOKASI TERHADAP LOYALITAS PELANGGAN PADA BENGKEL MOTOR XYZ DAAN MOGOT - Iswandir Iswandir (JURNAL MITRA MANAJEMEN, 2020)
ABSTRACTThis study aims to determine how much the relationship between service, image, and the location of the XYZ workshop and customer loyalty, using quantitative descriptive methods and the entire population is made sample = 59. Methods of data collection using observation techniques, interviews, and questionnaires. Statistical analysis used SPSS version 20.0. Service regression results Ŷ = 19.625 + 0.586, image regression results Ŷ = 39.920 + 0.861, location regression results Ŷ = 17.628 + 0.712, indicating the magnitude of the relationship between service, image, and location to customer loyalty (Y). The result of multiple regression 7, = 7,886 + 0,685X1 + 0,712X2 + 0,879X3, shows that the magnitude of the relationship between Service X1 is 0.689, Image X2 is 0.712, and Location X2 is 0.879 with a constant value of 7.886. From the results of the T test, it was obtained that the tcount was 17.948 greater than the ttable 2.769. This shows that service, image, and workshop location are simultaneously related to customer loyalty. The result of Multiple Determination shows the coefficient of determination 0.507 means that 50.70% is the contribution of service, image, and service variables, the remaining 49.30% is the contribution of other variables. Keywords: Motorcycle repair shop, service, image, location, customer loyalty